2020
DOI: 10.1024/1421-0185/a000241
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Value-Based Decision-Making Policies Using Genetic Programming

Abstract: Abstract. An important way to develop models in psychology and cognitive science is to express them as computer programs. However, computational modeling is not an easy task. To address this issue, some have proposed using artificial-intelligence (AI) techniques, such as genetic programming (GP) to semiautomatically generate models. In this paper, we establish whether models used to generate data can be recovered when GP evolves models accounting for such data. As an example, we use an experiment from decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In psychology, GEMS has successfully generated scientific theories semiautomatically for a number of experiments (Addis et al, 2016;Frias-Martinez & Gobet, 2007;Lane et al, 2016;Sozou et al, 2017). Although these are initial results that still need to be refined by future research, they establish the validity of the GEMS approach (e.g., Pirrone & Gobet, 2020, 2021.…”
Section: Semiautomatic Development Of Theoriesmentioning
confidence: 99%
“…In psychology, GEMS has successfully generated scientific theories semiautomatically for a number of experiments (Addis et al, 2016;Frias-Martinez & Gobet, 2007;Lane et al, 2016;Sozou et al, 2017). Although these are initial results that still need to be refined by future research, they establish the validity of the GEMS approach (e.g., Pirrone & Gobet, 2020, 2021.…”
Section: Semiautomatic Development Of Theoriesmentioning
confidence: 99%
“…The primary outcome of their study suggested that in musically untrained children, the connections between musical and cognitive abilities restrain to auditory short-term and working memory. In a contribution from the UK, Pirrone and Gobet (2020) provide evidence that genetic programming to semi-automatically generate computational models is a promising approach to recover data from various levels of complexity. By contrast, Burtscher and colleagues (2020) set out to further our understanding of how expertise affects communication and coordination processes in healthcare action teams.…”
mentioning
confidence: 99%